Fresno's Martin Luther King, Jr. March from City Hall to Saroyan Theatre - Watkins, Howard::::::::: (1987)
Marchers walking south on M Street; Roosevelt Black Student Union banner; Cantor Michael Loring and June Loring with guide dog, Toni and Ed Ames with guide dogs, Chris Petersen, ??, Mary Curry, ?, Karen Humphrey, ?, Dale Doig, ?, Rev. Chester Riggins, Les Kimber and ?walking arm in arm across street Construction crane and Brix Apartments in background